2021
DOI: 10.1108/gm-07-2020-0219
|View full text |Cite
|
Sign up to set email alerts
|

Tribal women’s work-life balance: an identity-based approach

Abstract: Purpose This paper aims to examine the work-life balance (WLB) experiences of tribal working women belonging to the matrilineal Khasi and Jaintia communities of Meghalaya, India, using an identity-based approach. Design/methodology/approach Semi-structured interviews conducted with 18 tribal women working in the formal sector helped generate descriptions of the subjective subliminal tensions they experienced in their efforts to balance work and home life. Findings Six key themes emerged: webs of role-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Some work-related antecedents such as WFC (Gupta and Srivastava, 2020), work overload (Poulose and Dhal, 2020), longer working hours, tight deadlines and lack of supervisor support (Nath and Dwivedi, 2020) resulted in reduced career commitment, increased turnover intention, increased work-related strain, reduced job satisfaction and low perceived WLB. Some positive measures such as participative leadership ( Bhumika, 2020) and workplace flexibility (Rastogi et al , 2018) resulted in better work environment and welfare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some work-related antecedents such as WFC (Gupta and Srivastava, 2020), work overload (Poulose and Dhal, 2020), longer working hours, tight deadlines and lack of supervisor support (Nath and Dwivedi, 2020) resulted in reduced career commitment, increased turnover intention, increased work-related strain, reduced job satisfaction and low perceived WLB. Some positive measures such as participative leadership ( Bhumika, 2020) and workplace flexibility (Rastogi et al , 2018) resulted in better work environment and welfare.…”
Section: Discussionmentioning
confidence: 99%
“…Though few studies did not mention the type of sampling technique used for data collection in specific. Maximum studies adopted sample size greater than 50 for their examination except for only Anand (2020), Nath and Dwivedi (2020) which used sample sizes of 15 and 18, respectively. Thematic and interpretive methods were used to analyze data obtained in qualitative studies, whilst statistical data analysis methods (correlation, regression, SEM, CFA, EFA, etc.)…”
Section: Research Questionsmentioning
confidence: 99%
“…Before the analysis, the researchers listened to the interview recording several times to understand the participants' views better. This enabled the authors to develop codes reflective of the data and literature on the KM enabler framework (Nath & Dwivedi 2021). This analytical approach in premised on an a priori coding where codes are developed from a literature review to support an investigation into a phenomenon (Nunes & Al-Mamari 2008).…”
Section: Methodsmentioning
confidence: 99%
“…The previous study has examined the impact of work pressure and family balance conflict on employees' physical and mental health as well as wellbeing. Identity theory suggested that work-life pressure and family-life balance conflict would have separate effects on employee mental health consequences (Nath, Dwivedi, 2021). This notion is backed up by a lot of evidence from the past findings (Frone et al, 1996;Casper et al, 2011;Madsen, Hammond, 2013;etc.).…”
Section: Work-life Balance and Mental Health In Organizationmentioning
confidence: 99%